The effects of hand tremors on the shooting performance of air pistol shooters with different skill levels - Liu, Y.; Hu, N.; Sun, M.; Qu, F.; Zhou, X. (Sensors, 2024)
Physiologic hand tremors are a critical factor affecting the aim of air pistol shooters. However, the extent of the effect of hand tremors on shooting performance is unclear. In this study, we aim to explore the relationship between hand tremors and shooting performance scores as well as investigate potential links between muscle activation and hand tremors. In this study, 17 male air pistol shooters from China`s national team and the Air Pistol Sports Center were divided into two groups: the elite group and the sub-elite group. Each participant completed 40 shots during the experiment, with shooters` hand tremors recorded using three-axis digital accelerometers affixed to their right hands. Muscle activation was recorded using surface electromyography on the right anterior deltoid, posterior deltoid, biceps brachii (short head), triceps brachii (long head), flexor carpi radialis, and extensor carpi radialis. Our analysis revealed weak correlations between shooting scores and hand tremor amplitude in multiple directions (middle-lateral, ML: r2 = -0.22, p < 0.001; vertical, VT: r2 = -0.25, p < 0.001), as well as between shooting scores and hand tremor complexity (ML: r2 = -0.26, p < 0.001; VT: r2 = -0.28, p < 0.001), across all participants. Notably, weak correlations between shooting scores and hand tremor amplitude (ML: r2 = -0.27, p < 0.001; VT: r2 = -0.33, p < 0.001) and complexity (ML: r2 = -0.31, p < 0.001) were observed in the elite group but not in the sub-elite group. Moderate correlation were found between the biceps brachii (short head) RMS and hand tremor amplitude in the VT and ML directions (ML: r2 = 0.49, p = 0.010; VT: r2 = 0.44, p = 0.025) in all shooters, with a moderate correlation in the ML direction in elite shooters (ML: r2 = 0.49, p = 0.034). Our results suggest that hand tremors in air pistol shooters are associated with the skill of the shooters, and muscle activation of the biceps brachii (long head) might be a factor affecting hand tremors. By balancing the agonist and antagonist muscles of the shoulder joint, shooters might potentially reduce hand tremors and improve their shooting scores.